PENGARUH KUALITAS SEKOLAH, BAURAN PROMOSI DAN LOKASI SEKOLAH TERHADAP JUMLAH SISWA SMA SWASTA DI KABUPATEN PRINGSEWU TAHUN PELAJARAN 20162017 - Heri Supranoto (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2017)
The purpose of this study was to determine the effect of school quality (X1), Promotion mix (X2), School location (X3) Against the number of students (Y). The type of this research is descriptive associative. Descriptive means describing the variables X1, X2, X3 dan Y, While the associative meaning seeks a relationship or influence between variables X1,X2, X3 and Y. This study uses ex post facto method, which is to test what has happened to the subject. The population in this study amounted to 24 schools, because the population is less than 100, the sampling technique in this study is to use saturated samples. All of the population is sampled. Based on the table, to test the above hypothesis is using statistic F. In the table it is explained that Fhitung = 10007.508With a level of significance 0,00. FhitungWith dk numerator = k and dk denominator = n-k-1 with α = 0,05 with Ftabel = F (0,05)(3; 103-3-1)  = F(0,05)(3:100) = 2,790. Therefore Fhitung  > Ftabel  or 10007.508> 2,790. Means, H0 is rejected and H1 accepted. With a level of significance 0,00. Means, H0 is rejected and H1 accepted. It means that, there is a significant influence among school quality (X1), Promotion mix (X2), School location (X3) Against the number of students (Y). Level determination of 0.997 or 99.7%, this means the variable number of students (Y) is affected by school quality (X1), Promotion mix  (X2), School location (X3) of 99,7%, The rest of 0.3% influenced by other factors not examined in this study. Keywords: Promotion mix and school location, School quality.